13 hours [large type] : the inside account of what really happened in Benghazi - Zuckoff, Mitchell (Twelve, Hachette Book Group, 2014)
The first account of the events of September 11, 2012, when terrorists attacked the U.S. State Department Special Mission Compound and a nearby CIA station called the Annex in Benghazi, Libya. A team of six American security operators fought to repel the attackers and protect the Americans stationed there. Those men went beyond the call of duty, performing extraordinary acts of courage and heroism, to avert tragedy on a much larger scale. This is their personal account of the thirteen hours of that now-infamous attack, setting the record straight on what happened during a night that has been shrouded in controversy.